The Effect of Health Education Course Review Horay Method and Video Media on Improvement of Personal Hygiene Ability in Children Age School - Novita Riya; Yuni Sufyanti Arief; Iqlima Dwi Kurnia (Universitas Airlangga, 2020)
Introduction: Personal hygiene problems that often occur in school-age children are related to hand hygiene and dental hygiene. This study aims to explain the effect of health education methods review horay courses and videos media on improving personal hygiene abilities.Methods: Quasy-experimental pretest-posttest design with control group design. A population of 150 students in Elementary School (ES) A of Surabaya and 123 students in ES B of Surabaya. The sample size was proportional to stratified cluster random sampling. A total of 72 respondents in ES A of Surabaya and ES B of Surabaya with 36 treatment groups and 36 control groups. The instrument used a questionnaire and an observation sheet (checklist). The analysis uses the Wilcoxon Signed Ranks Test and the Mann-Whitney U Test.Results: Wilcoxon Signed Ranks Test showed knowledge (p = 0.000), attitude (p = 0.000), hand hygiene practice (p = 0.000) and tooth brushing practice (p = 0.000). The value of p <0.05 then there was the effect of intervention courses review horay method and video to increase the ability of personal hygiene in school-age children. Mann-Whitney U Test results showed knowledge (p = 0.000), attitude (p = 0.000), hand hygiene practices (p = 0.000) and tooth brushing practice (p = 0.000). The value of p <0.05 then there was a mean difference in the level of personal hygiene ability between the treatment and control groups.Conclusion: Health education horay review course method and video media to improve the ability of personal hygiene in school-age children to increase knowledge, attitudes and actions in the form of hand hygiene and tooth brushing properly and correctly in the elementary school.